Karakteristik, Penanganan, dan Kandungan Mineral Keong Laut Neverita didyma - Aris Munandar; Sakinah Haryati; Rini Alfia; Fitriyani Fitriyani (Jurnal FishtecH, 2016)
Neverita didyma was a sea snail that included in the catch side from fishermen of Anadara granosa. The snail usually consumed with boiled and steamed. N. didyma can be used as a mineral source that needed by human. Information about characteristic of snail and its handling process on boat and collector was important. The aim of the research was to determine characteristic (rendemen and morphometric), handling process and mineral content of N. didyma. This research consisted of several stages. The stage was determination of characteristic of N. didyma, handling process and analisys of mineral content using Atomic Absorption Spectrophotometry (AAS). N. didyma had rendemen characteristic. each of characteristic was shell; 60.73%, meat 25% and offal 14.27%. Morphometric of snail was length 34.8 mm, width 28.33 mm and weight 12.86 g. Handling of N. didyma on boat and collector had not done well. mineral content of meat consisted of magnesium, potassium, sodium, calsium, phosporus, iron, zinc, and cooper.